GAGASAN KHALED ABOU EL FADL1 TENTANG PROBLEM OTORITARIANISME TAFSIR AGAMA PENDEKATAN HERMENEUTIK DALAM STUDI FATWA-FATWA KEAGAMAAN - Sanaky, Hujair (Al-Mawarid Jurnal Hukum Islam, 2005)
One of the famous Moslem scholar is Khaled Abou El Fadl. He has studied of religious fatwas that recorded in council religious legal opinion. The main problem that this scholar investigates regarding religious fatwas on gender. Abou El Fadl offers methodology of how to interpret ther meaning of the law texts, it is hermeneutic. The characteristics of this kind of methodology is that there is closed relation text, context, author, and interpreter reader). So, the meaning of Islamic law texts can be classified into two categories, authoritarianism and authoritative meaning. Departing from this, according to Abou El Fadl to understand the meaning of Islamic law texts in this era should consider hermeneutics. Kata kunci : menjunjung otoritas teks dan membatasi otoritarianisme pembaca.